A comprehensive, multi-objective optimization of solar-powered absorption chiller systems for air-conditioning applications. (15th January 2017) - Shirazi, Ali; Taylor, Robert A.; Morrison, Graham L.; White, Stephen D.
Highlights: Multi-objective optimization of solar single/multi-effect absorption chillers was conducted. Primary energy consumption and total annual cost were considered as the objectives. Optimized designs of the alternative configurations were compared. A detailed sensitivity analysis of the Pareto optimal solutions was investigated. Abstract: Solar heating and cooling (SHC) systems are currently under rapid development and deployment due to their potential to reduce the use of fossil fuel resources and to alleviate greenhouse gas emissions in the building sector – a sector which is responsible for ∼40% of the world energy use. Absorption chiller technology (traditionally powered by natural gas in large buildings), can easily be retrofitted to run on solar energy. However, numerous non-intuitive design choices must be analyzed to achieve the best techno-economic performance of these systems. To date, there has been little research into the optimal configurations among the long list of potential solar-driven absorption chiller systems. To address this lack of knowledge, this paper presents a systematic simulation-based, multi-objective optimization of three common, commercially available lithium bromide-water absorption chillers – single-effect, double-effect and triple-effect – powered by evacuated tube collectors (ETCs), evacuated flat plate collectors (EFPCs), and concentrating parabolic trough collectors (PTCs), respectively. To the best of authors' knowledge, this is the first study of its kind that compares the optimized designs of the most promising configurations of solar-assisted absorption chillers against a common set of energy, economic, and environmental metrics from a holistic perspective. A simulation model of these three configurations is developed using TRNSYS 17. A combined energy, economic, and environmental analysis of the modeled systems is conducted to calculate the primary energy use as well as the levelized total annual cost of each plant, which are considered as two conflicting objective functions. By coupling TRNSYS and MATLAB, a multi-objective optimization model is formulated using a genetic algorithm to simultaneously minimize these objectives, thereby determining a set of optimal Pareto solutions corresponding to each SHC configuration. The performance of the proposed systems at their optimal designs is then compared to that of a reference conventional system. A sensitivity analysis is also performed to assess the influence of fuel cost, capital cost of innovative components, and the annual interest rate on the Pareto front of optimal solutions. Overall, the optimization results reveal that of the proposed configurations, the SHC double-effect chiller has the best trade-off between the energetic, economic and environmental performance of the system, having a total cost of ∼0.7–0.9 M per year and reducing the annual primary energy use and CO2 emissions by 44.5–53.8% and 49.1–58.2% respectively (relative to the reference conventional system). With the high capital cost associated with these systems, government subsidies and incentives are still required in order for them to achieve satisfactory payback times and become cost-competitive with conventional HVAC systems.